Search for in vitro antibacterial efficacy of phytoconstituents of Acacia arabica leaf extracts against various serogroups of E. coli associated with diarrheal infections in ruminants - Biswas, Deboshree; Roymon, M G (Recent Research in Science and Technology, 2013)
The investigation was carried out in order to detect antibacterial activity of crude methanolic, acetone, chloroform and aqueous leaf extracts of Acacia arabica against four different E. coli strains E. coli O22, O11, O89 and O61 associated with diarrheal infections in ruminants. MIC of methanolic extract was observed to be ranged from 0.09 to 0.17 mg/ml where as acetone leaf extract ranged from 0.5 to 5 mg/ml whereas chloroform and aqueous leaf extract showed no inhibitory results against any tested organism.